Case report: Atypical lipomatous tumor of the thigh in a four-year-old girl - Ogawa, Itaru; Hakozaki, Michiyuki; Kaneuchi, Yoichi; Suzuki, Takeo; Nikaido, Takuya; Yamada, Shoki; Utsumi, Akihito; Hasegawa, Osamu; Sano, Hideki; Matsumoto, Yoshihiro (Frontiers in Oncology, 2024)
Atypical lipomatous tumors (ALTs) are locally aggressive adipocytic malignancies that frequently occur in middle-aged adults. We report the rare case of an ALT of the thigh that occurred in a 4-yearold girl. Since the tumor was initially diagnosed as a lipoblastoma by incisional biopsy, marginal resection was performed. Histopathological findings of the surgical specimen revealed the proliferation of mature and variously sized adipocytes, as well as ectopic ossification; these features differ from the typical findings of lipoblastoma. Immunohistochemical findings showed nuclear positivity for a murine double minute 2 (MDM2) and cyclin-dependent kinase 4 (CDK4) and negativity for pleomorphic adenoma gene 1 (PLAG1). Fluorescence in situ hybridization showed abnormal amplification of the MDM2 gene. The patient was thus finally diagnosed as having an ALT.No signs of local recurrence or metastasis were noted 1 year postoperatively. This case is instructive in the differential diagnosis of primary adipocytic tumors. Lipoblastomas are the most common adipocytic tumors in children, but if a tumor is located in the deep tissue or imaging findings are not typical, the possibility of ALT should be considered and immunohistochemistry for MDM2 and CDK4 should be added.